KONFLIK BATIN TOKOH SUZUHARA TOKO DALAM DORAMA MOTHER KARYA YUJI SAKAMOTO: KAJIAN PSIKOLOGI SASTRA - I Nyoman Rifno Riyadi; Ni Wayan Meidariani; Ni Luh Gede Meilantari (Jurnal Daruma : Linguistik, Sastra dan Budaya Jepang, 2021)
This study aims to study and describe the inner conflicts of Suzuhra Toko’s Character in the drama Mother. This type of study is descriptive-qualitative. The data source used in this study is the drama Mother. The data obtained were analyzed using Kurt Lewin’s psychodynamic theory. The data collection methods and techniques in this study used the observation method with the advanced technique of taking notes, namely by listening to the drama Mother, then recording the dialogue that showed inner conflict. Methods and data analysis techniques using qualitative descriptive methods described by informal methods, namely descriptions of ordinary words in Indonesian that are easy to understand. The results showed that the Suzuhara Toko character experienced approach-approach conflict, avoidance-avoidance conflict, and approach-avoidance conflict.